Split the party eaudiobook - Hayes, Drew (Spells, Swords, & Stealth, 2015)
Fleeing from a vengeful king has sent the former NPCs across Solium's borders, into the kingdom of Alcatham. As wanted fugitives, they head to the small farming village of Briarwillow, hoping to blend in, lay low, and avoid trouble at all costs. Unfortunately, Briarwillow has problems all its own, and its troubles quickly become theirs. If they hope to survive long enough to escape, they'll have to tackle an all-but-forgotten mystery buried at the town's border, as well as seek the wisdom of a mysterious group of mages. With time, magic, and at least one god against them, it will take everything they've got to save Briarwillow, and themselves.